Characterization of drug-release kinetics in trabecular bone from titania nanotube implants - Moom, Sin Aw; Khalid, Kamarul Ariffin; Gulati, Karan; J Atkins, Gerald; Pivonka, Peter; Findlay, David M.; Losic, Dusan (DOVE Medical Press, Auckland, 2012)
Purpose: The aim of this study was to investigate the application of the three-dimensional bone bioreactor for studying drug-release kinetics and distribution of drugs in the ex vivo cancellous bone environment, and to demonstrate the application of nanoengineered titanium (Ti) wires generated with titania nanotube (TNT) arrays as drug-releasing implants for local drug delivery